ANALISIS PERKEMBANGAN BAHASA DAN PEMEROLEHAN BAHASA ANAK USIA DINI - Sukat; Lina Putriyanti; Joko Sulianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Language development in early childhood is an important aspect in the child's growth and development stages. This process involves various abilities ranging from understanding to expression, as well as the use of language to interact with the surrounding environment. Early childhood language development starts from birth, from knowing the mother tongue as the first language to getting to know more complex languages. Language acquisition in early childhood is a complex process involving various factors, such as natural factors, cognitive factors, background factors and hereditary factors. This research provides a better understanding of the factors that influence language acquisition in early childhood and provides insight into how approaches can be applied to facilitate optimal language development in the early stages of a child's life.